2014
DOI: 10.1039/c3nr05780a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu, Zn and Cu/Zn brass alloy nanoparticles from metal amidinate precursors in ionic liquids or propylene carbonate with relevance to methanol synthesis

Abstract: Microwave-induced decomposition of the transition metal amidinates {[Me(C(N(i)Pr)2)]Cu}2 (1) and [Me(C(N(i)Pr)2)]2Zn (2) in the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIm][BF4]) or in propylene carbonate (PC) gives copper and zinc nanoparticles which are stable in the absence of capping ligands (surfactants) for more than six weeks. Co-decomposition of 1 and 2 yields the intermetallic nano-brass phases β-CuZn and γ-Cu3Zn depending on the chosen molar ratios of the precursors. Nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 89 publications
2
63
0
Order By: Relevance
“…Owing to the distinctive physicochemical properties of ILs (wide liquidus range, high redox and thermal stability, negligible vapor pressure, and tunable polarity) and their advantages over organic solvents, classic melts, or solid state reactions, their applications include separation techniques [7,8,9], lubrication [10], electrodeposition [11], acting as electrolytes in photovoltaic devices (e.g., solar cells) [12,13,14], catalysis for clean technology [15,16,17,18], polymerization processes [19], crystal engineering of a wide range of inorganic substances [20,21,22,23,24,25], and syntheses of new inorganic materials in general [23,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. Recently, several comprehensive reviews on syntheses of inorganic compounds in ILs have been published by Taubert [52], Feldmann [28], Dehnen [51], Janiak [42,53], Scrosati and Passerini [48], Morris [54], Mudring [55], Prechtl [56], Zhu [57], Dai [58], and Ruck [23,27,59] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the distinctive physicochemical properties of ILs (wide liquidus range, high redox and thermal stability, negligible vapor pressure, and tunable polarity) and their advantages over organic solvents, classic melts, or solid state reactions, their applications include separation techniques [7,8,9], lubrication [10], electrodeposition [11], acting as electrolytes in photovoltaic devices (e.g., solar cells) [12,13,14], catalysis for clean technology [15,16,17,18], polymerization processes [19], crystal engineering of a wide range of inorganic substances [20,21,22,23,24,25], and syntheses of new inorganic materials in general [23,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. Recently, several comprehensive reviews on syntheses of inorganic compounds in ILs have been published by Taubert [52], Feldmann [28], Dehnen [51], Janiak [42,53], Scrosati and Passerini [48], Morris [54], Mudring [55], Prechtl [56], Zhu [57], Dai [58], and Ruck [23,27,59] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanide-based solutions-which are not desirable due to environmental issues-were used as deposition electrolyte for Zn-Cu coatings in industry [25,26]. To solve these issues, environmentally-friendly and cyanide-free media including non-aqueous (ionic liquids [27] and deep eutectic solvents [28]) and aqueous media (gluconate [29], EDTA [30,31], mannitol [32], tartrate [33], ammonia [34], and pyrophosphate-based complex solutions [35,36]) have been used for Zn-Cu deposition. Specifically, pyrophosphate deposition bath is an environmentally friendly electrolyte [37], and metals/alloys obtained in this electrolyte do not produce their oxide/hydroxide forms [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Although the coinage metals are normally used in elemental form for such applications, there is also some interest in using their alloys [1]. For example, it has been demonstrated that nanoparticles can be fabricated from Cu-Zn alloys [2][3][4][5][6][7] and that a surface plasmon resonance can be sustained [4,7]. The color of the bulk CuZn brasses varies with the Zn content, as does the energy of the plasmon resonance in nanoparticles.…”
Section: Introductionmentioning
confidence: 99%